Tourism as a development factor in the light of regional development theories - Butowski, Leszek (Turyzm/Tourism, 2010)
The article concerns theoretical positions on the influence of tourism on regional and local development. The adaptation possibilities of chosen regional development theories for the research needs of the tourism influence on regional development are presented. Four groups were analysed: 1) endogenous development theories 2) network development theories 3) economic base theories 4) polarisation theories. Using works based on these there has been an attempt to indicate the theoretical basis of tourism growth as a factor of regional development.